Penerapan Model Pembelajaran Tematik dalam Meningkatkan Kemampuan Koneksi Matematis pada Siswa Sekolah Dasar - Supriatin, Atin (LP2M IAIN Palangka Raya, 2009)
The experimental design of this study was used the post and pretest control group design. The main purpose of this study is to defferentiate between the studentsâ mathematics connection ability improvement by using thematic learning applied and habitual learning. It was done to all the students of the third class of SDN 2 Kayuambon Lembang Bandung Barat Regency. The total of the population were 74 students. Based on the data analysis, the improvement of the students mathematics connection between of the classess were different. The differentiation of the studentsâ ability improvement were tested statatically two way anova test by using the significant level (Î±) = 0,05. Based on the experimental result, it could be concluded that the studentsâ mathematics connection ablity improvement by thematic learning was better than the habitual learning.Â Â Â Â Â